Peran Modal Sosial dalam Strategi Kampanye Pemilihan Umum Raya Mahasiswa (Studi Kasus Pemira UNNES Tahun 2024) - Adhitya Deva; Kuncoro Bayu Prasetyo (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2026)
Pemilihan Umum Raya (Pemira) serves as a campus democratic arena that reflects the dynamics of student politics, particularly in the practice of candidate campaign strategies. One of the important factors influencing this process is social capital, which includes social networks, collective norms, and trust. This study aims to analyze the role of social capital in student campaign strategies during the 2024 UNNES Pemira and to explain how social capital is utilized by candidates to gain political support. This research employs a qualitative descriptive approach with data collection techniques consisting of semi-structured interviews, observation, and documentation. The research informants include Pemira candidates, campaign teams, observers of the election process, and student voters from various faculties. Data were analyzed using the interactive model of Miles and Huberman, which includes data condensation, data display, and conclusion drawing. The findings show that candidates with broader social networks, strong organizational backgrounds, and higher levels of trust among students and supporter groups tend to have advantages in mobilizing political support. Social capital is utilized through cross-faculty personal relations, informal support from extra-campus organizations, and the use of leadership track records to build voter trust. In contrast, candidates with limited social capital face greater challenges in expanding their voter base and optimizing campaign activities. This study provides empirical contributions to the study of campus political sociology and strengthens the understanding of the role of social capital in student democratic practices.